Pnpla3I148M knockin mice accumulate PNPLA3 on lipid droplets and develop hepatic steatosis. Issue 1 (1st October 2014) - Smagris, Eriks; BasuRay, Soumik; Li, John; Huang, Yongcheng; Lai, Ka‐man V.; Gromada, Jesper; Cohen, Jonathan C.; Hobbs, Helen H.
<x xml:space="preserve">Abstract</x> A sequence polymorphism (rs738409, I148M) in patatin‐like phospholipid domain containing protein 3 (PNPLA3) is strongly associated with nonalcoholic fatty liver disease (NAFLD), but the mechanistic basis for this association remains enigmatic. Neither ablation nor overexpression of wild‐type PNPLA3 affects liver fat content in mice, whereas hepatic overexpression of the human 148M transgene causes steatosis. To determine whether the 148M allele causes fat accumulation in the liver when expressed at physiological levels, we introduced a methionine codon at position 148 of the mouse Pnpla3 gene. Knockin mice had normal levels of hepatic fat on a chow diet, but when challenged with a high‐sucrose diet their liver fat levels increased 2 to 3‐fold compared to wild‐type littermates without any associated changes in glucose homeostasis. The increased liver fat in the knockin mice was accompanied by a 40‐fold increase in PNPLA3 on hepatic lipid droplets, with no increase in hepatic PNPLA3 messenger RNA (mRNA). Similar results were obtained when the catalytic dyad of PNPLA3 was inactivated by substituting the catalytic serine with alanine (S47A). Conclusion: These data provide the first direct evidence that physiological expression of PNPLA3 148M variant causes NAFLD, and that the accumulation of catalytically inactive PNPLA3 on the surfaces of lipid droplets is associated with the accumulation of TG in the liver. (Hepatology 2015;61:108–118)